Protocol for MRI-guided virus injection in macaque deep brain regions - Panke Yu; Zhiting Zhang; Yuyin Wang; Ji Dai (STAR Protocols, 2023)
Summary: Effective delivery of viruses into required brain regions is critical to the success of optogenetic or chemogenetic experiments. However, in monkeys, due to the large size and heterogeneity of their brain, precise injections in deep brain regions have been challenging. Here, we present a protocol for virus injection in monkey deep brain regions under the guidance of MRI. We describe the steps for installing the guiding grid, MRI scanning, MRI-based localization, and virus injection.For complete details on the use and execution of this protocol, please refer to Chen et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.